Considerations for the Bioanalytical Part of Equivalence Studies of Biosimilar Nadroparin Calcium - V. M. Kosman; M. V. Karlina; N. M. Faustova; E. A. Ezhova; I. G. Kotelnikova; V. G. Makarov; M. N. Makarova (Регуляторные исследования и экспертиза лекарственных средств, 2023)
According to current regulatory views, a comparative study of the pharmacodynamics (PD) of low molecular weight heparin (LMWH) products and confirmation of their equivalence require comparing three PD markers: the anti-Xa activity, the anti-IIa activity, and the tissue factor pathway inhibitor (TFPI) concentration. The aim of this study was to analyse the features specific to the bioanalytical part of an equivalence study of a nadroparin calcium biosimilar after single subcutaneous administration. Material and methods: the anti-Xa and anti-IIa activity values and TFPI content were determined in human plasma samples obtained after single subcutaneous administration of the test and the reference product in the same dose, using commercially available reagent kits and pre-validated assays. The authors calculated the main PD parameters (surrogate pharmacokinetic markers), namely the maximum activity or concentration (Amax or Cmax), time to maximum activity or concentration (Tmax), area under the activity–time (or concentration–time) curve (AUC ), and half-life period (T1/2), by means of model-independent statistical moment analysis and carried out further statistical testing of the parameters. Results: the anti-Xa activity and TFPI concentration results provided for  the  possibility  of  calculating  and  comparing  the PD parameters (Amax or Cmax, AUC0-24, AUC0-∞, Tmax, T1/2) and estimating the confidence intervals that are necessary to confirm the bioequivalence of the studied products. The anti-IIa activity data had a characteristic pattern of slight fluctuations around one level, which prevented the calculation and comparison of PD parameters. Conclusion: the study identified specific features to consider when planning comparative PD studies of nadroparin calcium products. Firstly, it is feasible to divide samples into two test aliquots (one for anti-Xa and anti-IIa activity determination, the other for TFPI analysis) at the moment of collection in order to perform the analytical step correctly. Secondly, there is no need in full validation for the bioanalytical assays of the anti-Xa and anti-II activity and TFPI content in human plasma validated in the concentration ranges of 0.024–0.182 IU/mL, 0.0069–0.052 IU/mL and 1.56–100 ng/mL, respectively; a confirmation that the active ingredient does not interfere with the analytical procedure is adequate for the purpose. Finally, the data obtained may not allow for calculating PD parameters and comparing confidence intervals for all three markers. The listed considerations may be relevant for other LMWH products as well.